Faktor-faktor yang Berhubungan dengan Kelelahan Kerja pada Pekerja Bagian Operator SPBU di Kecamatan Indramayu Tahun 2022 - Nanda Putri Lisa Ardiyanti Tarwijah (Yayasan Pendidikan Medika Indonesia, 2022)
Psychological disorders in the form of feelings of severe fatigue and lead to depression will become the number two killer disease heart disease. More than 65% of workers in Indonesia come to the company's polyclinic with complaints of work fatigue. This study aims to determine the factors associated with work fatigue among workers in the gas station operator division in Indramayu District in 2022. The sample consists of 42 people with a total sampling. This type of research is quantitative with a cross sectional. The data analysis used is univariate analysis and bivariate analysis with chi square test. The results of this study indicate that there is a relationship between age and work fatigue for workers in the gas station operator division in Indramayu District in 2022 with a p-value = 0.001 (p<0.05). There is a relationship between working period and work fatigue for workers in the gas station operator division in Indramayu District in 2022 with a p-value = 0.001 (p<0.05). It is recommended to reduce work fatigue, gas station operator workers pay more attention to time to rest or pause when they feel indications of physical fatigue because standing position continuously. If permitted, workers can prepare sitting chairs at the workplace so that workers can rest comfortably without leaving the workplace. Keywords: Age, Working Period, Work Fatigue, Gas Station Operators.